2013
DOI: 10.7231/jon.2013.24.1.045
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Comparison of Efficacy of Needle-Embedding Therapy with Acupuncture for Chronic Tension-type Headache Patients

Abstract: Objectives : The purpose of this study was to compare the efficacy of Needle-Embedding Therapy with Acupuncture for Chronic Tension-type Headache (CTTH) patients. Methods : The study recruited Chronic Tension-type Headache patients. A total of twenty-six patients were divided into 2 groups. 13 subjects were placed into a needle-embedding therapy group and 13 subjects into an acupuncture therapy group by a randomization table. The needle-embedding therapy group was treated with needle-embedding at Fengchi (GB20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Thread-embedding acupuncture first originated from the idea of holding acupuncture needles steady because to treat a chronic disease it is necessary to place the needle in deeper and keep it there longer [49]. Bae et al [36] divided chronic tension headache patients into a thread-embedding acupuncture group and the acupuncture group, and performed acupuncture on the left and right of Fengchi (GB20) in the Wangu (GB12) direction. The study reported that since thread-embedding acupuncture showed similar pain-relieving effects to traditional acupuncture treatment, and had a longer-lasting effect, it could be applied efficiently for treatment intervals and frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thread-embedding acupuncture first originated from the idea of holding acupuncture needles steady because to treat a chronic disease it is necessary to place the needle in deeper and keep it there longer [49]. Bae et al [36] divided chronic tension headache patients into a thread-embedding acupuncture group and the acupuncture group, and performed acupuncture on the left and right of Fengchi (GB20) in the Wangu (GB12) direction. The study reported that since thread-embedding acupuncture showed similar pain-relieving effects to traditional acupuncture treatment, and had a longer-lasting effect, it could be applied efficiently for treatment intervals and frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Except for 2002, 2014, 2015, and 2016, studies had been conducted consistently. Out of the 41 studies, there were 18 case reports [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], 9 case series [24][25][26][27][28][29][30][31][32], 9 randomized controlled trials [33][34][35][36][37][38][39][40][41], and 2 non-randomized controlled trials [42,43] (Tables 1-5).…”
Section: Classification By Yearmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee's embedding therapy study 11) was reported about Improvement Against Facial Wrinkles, Han 12) reported the efficacy of embedding therapy to facial palsy, Yoon's embedding therapy study 13) was reported about Androgenetic alopecia in woman, Bae's embedding therapy study 14) was reported about chronic tension type Headache, Lee's embedding therapy study 15) was reported about lumbar disc herniation and Lee's embedding therapy study 16) was reported about shoulder pain in behcet disease. Like this, embedding therapy was reported used in not only cosmetic surgery but also musculoskeletal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…์ด๋ ‡๊ฒŒ ๋งค์„ ์š”๋ฒ•์˜ ๊ด‘๋ฒ”์œ„ํ•œ ์  ์‘์ฆ์—๋„ ๋ถˆ๊ตฌํ•˜๊ณ  ์ตœ๊ทผ ๊ตญ๋‚ด์˜ ๋งค์„ ์š”๋ฒ•์— ๋Œ€ํ•œ ์—ฐ๊ตฌ๋Š” ๋ฏธ์šฉ ์„ฑํ˜•๋ถ„์•ผ์˜ ๊ด€์‹ฌ์ด ๋†’์•„์ง์— ๋”ฐ๋ผ ์„ฑํ˜• ๋˜๋Š” ๋น„๋งŒ ์น˜ ๋ฃŒ์— ๊ด€๋ จ๋œ ์—ฐ๊ตฌ๊ฐ€ ์ฃผ๋กœ ๋ณด๊ณ ๋˜์—ˆ๋‹ค[6][7][8][9][10][11][12] . ๊ทธ ์™ธ์— ๋งŒ์„ฑ ๋‘ ํ†ต ํ™˜์ž20) ๋‚˜ ์น˜๋งค ํ™˜์ž 21) ์—๊ฒŒ ์ ์šฉํ•œ case๋„ ์žˆ์—ˆ์œผ๋‚˜, ๊ทผ ๊ณจ๊ฒฉ๊ณ„๋‚˜ ๊ธฐํƒ€ ๋™ํ†ต์„ฑ ์งˆํ™˜์— ์‘์šฉ๋œ ๊ฒฝ์šฐ๋Š” Lee et al 13) ์˜ ์š”์ถ” ์ถ”๊ฐ„ํŒ ํƒˆ์ถœ์ฆ์— ์‘์šฉํ•œ ๊ฒฝ์šฐ์™€ Lee et al 14) ์˜ ๋ฐœ๋ชฉ์ธ ๋Œ€ ์†์ƒ์— ์‘์šฉํ•œ ๊ฒฝ์šฐ ์™ธ์—๋Š” ํ™•์ธํ•˜์ง€ ๋ชปํ•˜์˜€๋‹ค. ๋ณธ ์ฆ๋ก€์—์„œ๋Š” ์–ด๊นจ ๊ด€์ ˆํ†ต์„ ์ฃผ์†Œ๋กœ ํ•œ ๋ฒ ์ฒดํŠธ๋ณ‘ ํ™˜์ž ์—๊ฒŒ ์นจ์น˜๋ฃŒ์™€ ํ•จ๊ป˜ ๋งค์„ ์š”๋ฒ•์„ ๋ณ‘ํ–‰ํ•˜์—ฌ ํ†ต์ฆ ๊ฐ์†Œ์™€ ์šด ๋™๋ฒ”์œ„์˜ ํ˜ธ์ „ ํšจ๊ณผ๊ฐ€ ์žˆ์—ˆ๋‹ค.…”
unclassified